A Modification of Unitary ESPRIT Method for Data Processing in Planar Phased Antenna Arrays - M. A. Gladysheva; A. V. Nemov (Известия высших учебных заведений России: Радиоэлектроника, 2016)
A modification of Unitary ESPRIT method of evaluation of an angular spectrum for planar phased antenna arrays (PAA) with regular structure of receiving elements arrangement is described. The structure regularity is necessary to split the PAA into identical sub-arrays displaced in space. Super-resolution of two emitters is confirmed experimentally in an anechoic chamber using a hexagonal planar PAA.